Characterization of dynamic compressive strength and impact release energy of Al/PTFE energetic materials reinforced by aluminum honeycomb skeleton. (1st June 2020) - Tang, Enling; He, Zhenhui; Chen, Chuang; Han, Yafei
Abstract: The insufficient dynamic compressive strength of the Al/PTFE energetic material with traditional ingredients has seriously restricted its application in the field of national defence. However, the improvement of strength must be at the expense of activity. In view of the contradiction, this paper pioneers aluminum honeycomb skeleton reinforcement method to achieve both strength and activity. On the basis of traditional ingredients Al/PTFE (mass percentage of 26.5%/73.5%), three types of energetic materials were prepared by cold pressing sintering process by adding different aluminum honeycomb skeletons with arm lengths of 1 mm, 1.5 mm and 2 mm, respectively. The dynamic compressive strengths of the specimen are obtained by using self-built Split Hopkinson Pressure Bar (SHPB) loading system and high-speed camera acquisition system. Meanwhile, the impact reaction release energies are also evaluated experimentally by using the one-stage light gas gun loading system combined with the transient optical fiber pyrometer measurement system, the overpressure measurement system and the infrared thermal imager measurement system. In term of dynamic compressive strength and impact reaction release energy, the performances of three types of Aluminum honeycomb reinforced energetic material were compared with those of traditional ingredients energetic material. The experimental results show that compared with the strength (25.17 MPa) of traditional ingredients Al/PTFE energetic material, the strengths of three kinds of energetic materials reinforced by aluminum honeycomb framework with arm lengths of 1 mm, 1.5 mm and 2 mm are 1.5, 3.1 and 2.2 times that of the traditional ingredients Al/PTFE, respectively; Especially, at the impact velocity of 510 m/s, the release energy of three kinds of Al/PTFE energetic materials reinforced by aluminum honeycomb framework with arm lengths of 1 mm, 1.5 mm and 2 mm were 2.52 kJ/g, 1.94 kJ/g and 2.40 kJ/g, respectively. However, the release energy of traditional ingredients Al/PTFE energetic material was only 1.85 kJ/g. Compared with the traditional ingredients Al/PTFE, the compressive strengths and release energies of three kinds of energetic materials reinforced by different arm lengths of Aluminum honeycomb were significantly improved under the same impact conditions.